RISK ASSESSMENT FOR THE POPULATION OF SAINT-PETERSBURG FROM RESIDENTIAL EXPOSURE TO RADON - D. V. Kononenko (Радиационная гигиена)
The paper presents the results of risk assessment for the population of Saint-Petersburg from residential exposure to radon and progeny considering interaction with tobacco smoking. U.S. EPA model was used. About 17% of lung cancer deaths in the general population could be radon-induced and the lifetime attributable risk for the population is about 8%.